2020
DOI: 10.1186/s12958-020-00623-x
|View full text |Cite
|
Sign up to set email alerts
|

Does the sex ratio of singleton births after frozen single blastocyst transfer differ in relation to blastocyst development?

Abstract: Purpose: To investigate the associations between blastocyst development and the sex ratio (male:female) among singleton live births resulting from single-blastocyst frozen embryo transfer (FET) cycles. Methods: Patients with singleton live births following the first autologous single FET of non-preimplantation genetic testing (PGT) blastocysts in a single reproductive medicine department between January 2015 and February 2019 were included in this retrospective study. The primary outcome measure was the single… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 32 publications
3
26
0
Order By: Relevance
“…A previous study has suggested that low sperm motility in IVF is associated with an increase in female/male ratio ( Arikawa et al , 2016 ). In addition, single poor-quality embryo transfers in frozen cycles have a higher chance of resulting in a female infant ( Oron et al , 2014 ; Lou et al , 2020 ). Consistent with these studies, our study shows poor quality blastocyst transfer can result in a higher rate of female live birth than the transfer of a good quality blastocyst transfer as defined by conventional embryo morphological grading.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has suggested that low sperm motility in IVF is associated with an increase in female/male ratio ( Arikawa et al , 2016 ). In addition, single poor-quality embryo transfers in frozen cycles have a higher chance of resulting in a female infant ( Oron et al , 2014 ; Lou et al , 2020 ). Consistent with these studies, our study shows poor quality blastocyst transfer can result in a higher rate of female live birth than the transfer of a good quality blastocyst transfer as defined by conventional embryo morphological grading.…”
Section: Discussionmentioning
confidence: 99%
“…The cleavage embryos and blastocysts were scored by the same experienced embryologist, thus eliminating intra-embryologist bias when evaluating embryos. The frozen-thawed procedure is described in detail elsewhere ( 13 ).…”
Section: Methodsmentioning
confidence: 99%
“…After the biopsy, the blastocyst were vitrificated using Cryotop® (Kitazato Corporation, Shizuoka, Japan) [13] . The vitri ed-warmed procedure has been described in detailed previously [14] .…”
Section: Laboratory Protocolsmentioning
confidence: 99%